Evidence of Added Worker Effect from the 2008 Economic Crisis - Sinem H. Ayhan (Institute for the Study of Labor (IZA), 2015)
This paper contributes to the research on interdependencies in spousal labor supply by analyzing labor supply response of married women to their husbands' job losses ("added worker effect"). It empirically tests the hypothesis of added worker effect relying on a case study on Turkey during the global economic crisis of 2008. Identification is achieved by exploiting the exogenous variation in the output of male-dominated sectors that were hit hard by the crisis and the high degree of gender segmentation that characterizes the Turkish labor market. Findings based on the instrumental variable approach suggest that the probability of entering the labor force for a woman increases by up to 29% in response to her husband's unemployment. However the effect is not contemporaneous; it appears with a quarter of lag and remains existent only for two quarters.
Keywords: C26; D10; J16; J22; 330; spousal labor supply; added worker effect; discouraged worker effect; global economic crisis